2005
DOI: 10.1111/j.1420-9101.2005.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Male sterility at extreme temperatures: a significant but neglected phenomenon for understanding Drosophila climatic adaptations

Abstract: The thermal range for viability is quite variable among Drosophila species and it has long been known that these variations are correlated with geographic distribution: temperate species are on average more cold tolerant but more heat sensitive than tropical species. At both ends of their viability range, sterile males have been observed in all species investigated so far. This symmetrical phenomenon restricts the temperature limits within which permanent cultures can be kept in the laboratory. Thermal heat st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
186
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(202 citation statements)
references
References 49 publications
12
186
1
3
Order By: Relevance
“…Other studies have shown similar declines in trap captures as well as reductions in survival and fecundity at high temperatures (David et al 2005;Kinjo et al 2014;Tochen et al 2014). The negative effects of high summer temperatures on SWD may explain why SWD has not become a pest of commercial stone fruit and grapes, which are primarily harvested from July to October in the San Joaquin Valley.…”
Section: High Temperature Effects On Capturesmentioning
confidence: 71%
“…Other studies have shown similar declines in trap captures as well as reductions in survival and fecundity at high temperatures (David et al 2005;Kinjo et al 2014;Tochen et al 2014). The negative effects of high summer temperatures on SWD may explain why SWD has not become a pest of commercial stone fruit and grapes, which are primarily harvested from July to October in the San Joaquin Valley.…”
Section: High Temperature Effects On Capturesmentioning
confidence: 71%
“…Therefore we suggest that our findings of Drosophila immune response genes being responsive to YRV are most likely explained by variation in noncoding components of the Y chromosome, such as repeat copy number. D. melanogaster populations from France and India are known to differ in the thermal sensitivity of spermatogenesis (Rohmer et al 2004;David et al 2005), with temperate and tropical Y chromosomes contributing substantially to this difference. Among genes that show YRV in at least two of the three backgrounds, we find candidates known to be structural constituents of cytoskeleton (nod, CG9279, and tm2) and lipid metabolism (CG9914, CG17292, CG9458, CG11426, CG6295, CG6277, CG18815, and CG31872).…”
Section: Discussionmentioning
confidence: 99%
“…Spermatogenesis in Drosophila males is extremely sensitive to heat, with males becoming sterile anywhere from 23°in heatsensitive species to 31°in heat-tolerant species (Chakir et al 2002;David et al 2005). In D. melanogaster, Rohmer et al (2004) found that differences between Y chromosome lineages from tropical and temperate regions are responsible for much of the variation in thermal sensitivity of spermatogenesis.…”
mentioning
confidence: 99%
“…Instead, most if not all of the~14 protein-coding genes present on the Y chromosomes of Drosophila melanogaster, D. simulans and other closely related species have male-specific functions and are exclusively expressed in the testis (Gepner and Hays, 1993;Carvalho et al, 2000;Carvalho et al, 2001;Vibranovski et al, 2008). Nevertheless, a suite of studies have shown that genetic variation present on the Y of Drosophila underlie phenotypic variation in male fitness (Chippindale and Rice, 2001;Yee et al, 2015), sex ratio distortion (Carvalho et al, 1997;Montchamp-Moreau et al, 2001;Branco et al, 2013a, b), tolerance to temperature extremes (Rohmer et al, 2004;David et al, 2005), behavior (Stoltenberg and Hirsch, 1997;Huttunen and Aspi, 2003), gene expression (Lemos et al, 2008;Sackton et al, 2011;Branco et al, 2013a, b) and chromatin states in somatic tissues .…”
Section: Introductionmentioning
confidence: 99%